Changes in Pediatric Heart Transplant Hospitalization Costs Over Time. Issue 10 (October 2018) - Godown, Justin; Thurm, Cary; Hall, Matt; Soslow, Jonathan H.; Feingold, Brian; Mettler, Bret A.; Smith, Andrew H.; Bearl, David W.; Dodd, Debra A.
Abstract : Background: Despite significant changes in the past decade for children undergoing heart transplantation, including the evolution of mechanical circulatory support and increasing patient complexity, costs and resource utilization have not been reassessed. We sought to use a novel linkage of clinical-registry and administrative data to examine changes in hospitalization costs over time in this population. Methods: We identified all pediatric heart transplant recipients in a unique linked Pediatric Health Information System/Scientific Registry of Transplant Recipients data set (2002-2016). Hospital costs were estimated from charges using cost-to-charge ratios, inflated to 2016 dollars. Severity-adjusted costs were calculated using generalized linear mixed-effects models. Costs were compared across 3 eras (era 1, 2002-2006; era 2, 2007-2011; and era 3, 2012-2016). Results: A total of 2896 pediatric heart transplant recipients were included: era 1, 649 (22.4%); era 2, 1028 (35.5%); and era 3, 1219 (42.1%). Extracorporeal membrane oxygenation support at transplant decreased over time, concurrent with an increase in ventricular assist device–supported patients. Between era 1 and era 2, there was an increase in pretransplant hospitalization costs (US 343 692 vs US 435 554; P < 0.001). However, between era 2 and era 3, there was a decline in total (US 906 454 vs US 767 221; P < 0.001), pretransplant (US 435 554 vs US 353 364; P < 0.001), and posttransplant (US 586 133 vs US 508 719; P = 0.002) hospitalization costs. Conclusions: Concurrent with the increase in utilization of ventricular assist device support, there has been an increase in pretransplant costs associated with pediatric heart transplantation. However, in the most recent era, costs have declined. These findings suggest the evolution of more cost-effective management strategies, which may be related to shifts in the approach to pediatric mechanical circulatory support. Abstract : Pretransplant costs associated with pediatric heart transplantation has increased, but the most recent era costs have declined with the evolution of more cost-effective management strategies, which may be related to shifts in the approach to pediatric mechanical circulatory support.